Tracking an Unusual Carbapenemase-producing Organism from Drains to Patient Using Whole Genome Sequencing. (4th October 2017) - Ramsburg, Amanda M; Weingarten, Rebecca A; Conlan, Sean P; Dekker, John P; Michelin, Angela V; Odom, Robin T; Bordner, MaryAnn; Zellmer, Caroline J; Henderson, David K; Segre, Julia A; Frank, Karen M; Palmore, Tara N
Abstract: Background: The NIH Clinical Center conducts patient and environmental surveillance for carbapenemase-producing organisms (CPO). Previous investigation revealed that sink drains can become colonized with CPO. Subsequent surveillance targets included potential aqueous reservoirs, such as floor drains of environmental services (EVS) closets. Methods: Premoistened swabs were used to culture sink drains, floor drains, and equipment for CPO. Perirectal swabs were ordered monthly for all patients in non-behavioral health wards. Specimens were plated to CRE- and ESBL-selective media, and colonies identified by MALDI-TOF. The presence of the bla KPC gene was confirmed by PCR. When environmental CPO isolates were detected, EVS procedures and practices were reviewed. Results: In June 2016, bla KPC + Leclercia adecarboxylata was isolated from an EVS closet floor drain, and in August 2016, from drains in four additional closets. In the previous 10 years, Leclercia sp. was isolated just once from a clinical culture. In September 2016, routine surveillance revealed new-onset bla KPC + L. adecarboxylata colonization in a stem cell transplant recipient. Investigation included 33 cultures collected from sink and floor drains, EVS equipment, and other items. EVS equipment, especially mop buckets, were identified as a likely point source due to their use in patient care areas and closets with contaminated floor drains. Among seven mop buckets sampled, one grew bla KPC + L. adecarboxylata . Whole genome sequencing demonstrated genetic relatedness of the Leclercia isolates. Floor cleaner was changed to a disinfectant solution. Extensive decontamination of 67 EVS closets and equipment was performed urgently. No further patient or environmental cultures have grown bla KPC + L. adecarboxylata. Conclusion: The recovery of a highly unusual organism, rarely found in clinical specimens, that was also carrying a bla KPC + plasmid, allowed us to detect environmental spread of this organism in the hospital. The ability to track this organism using genome sequencing provided strong evidence of the mode of spread, leading to effective remediation. No evidence-based methods exist for remediating drain contamination, which can serve as a potential reservoir for transmission. Disclosures: All authors: No reported disclosures.